Single-stranded nucleic acids promote SAMHD1 complex formation - Tüngler, Victoria (2013)
SAM domain and HD domain-containing protein 1 (SAMHD1) is a dGTP-dependent triphosphohydrolase that degrades deoxyribonucleoside triphosphates (dNTPs) thereby limiting the intracellular dNTP pool. Mutations in SAMHD1 cause Aicardi–Goutieres syndrome (AGS), an inflammatory encephalopathy that mimics congenital viral infection and that phenotypically overlaps with the autoimmune disease systemic lupus erythematosus. Both disorders are characterized by activation of the antiviral cytokine interferon-α initiated by immune recognition of self nucleic acids. Here we provide first direct evidence that SAMHD1 associates with endogenous nucleic acids in situ. Using fluorescence cross-correlation spectroscopy, we demonstrate that SAMHD1 specifically interacts with ssRNA and ssDNA and establish that nucleic acid-binding and formation of SAMHD1 complexes are mutually dependent. Interaction with nucleic acids and complex formation do not require the SAM domain, but are dependent on the HD domain and the C-terminal region of SAMHD1. We finally demonstrate that mutations associated with AGS exhibit both impaired nucleic acid-binding and complex formation implicating that interaction with nucleic acids is an integral aspect of SAMHD1 function.